Oxide/ZIF-8 Hybrid Nanofiber Yarns: Heightened Surface Activity for Exceptional Chemiresistive Sensing - Kim, Dong-Ha; Chong, Sanggyu; Park, Chungseong; Ahn, Jaewan; Jang, Ji-Soo; Kim, Jihan; Kim, Il-Doo (WILEY-V C H VERLAG GMBH, 2022)
Though highly promising as powerful gas sensors, oxide semiconductor chemiresistors have low surface reactivity, which limits their selectivity, sensitivity, and reaction kinetics, particularly at room temperature (RT) operation. It is proposed that a hybrid design involving the nanostructuring of oxides and passivation with selective gas filtration layers can potentially overcome the issues with surface activity. Herein, unique bi-stacked heterogeneous layers are introduced; that is, nanostructured oxides covered by conformal nanoporous gas filters, on ultrahigh-density nanofiber (NF) yarns via sputter deposition with indium tin oxide (ITO) and subsequent self-assembly of zeolitic imidazolate framework (ZIF-8) nanocrystals. The NF yarn composed of ZIF-8-coated ITO films can offer heightened surface activity at RT because of high porosity, large surface area, and effective screening of interfering gases. As a case study, the hybrid sensor demonstrated remarkable sensing performances characterized by high NO selectivity, fast response/recovery kinetics (>60-fold improvement), and large responses (12.8-fold improvement @ 1 ppm) in comparison with pristine yarn@ITO, especially under highly humid conditions. Molecular modeling reveals an increased penetration ratio of NO over O-2 to the ITO surface, indicating that NO oxidation is reliably prevented and that the secondary adsorption sites provided by the ZIF-8 facilitate the adsorption/desorption of NO, both to and from ITO.